2000
DOI: 10.3184/030823400103166913
|View full text |Cite
|
Sign up to set email alerts
|

The Stereoselective Synthesis and the Nitrogen Interconversion Studies of 2-(tert-butoxymethyl)-1-[NT-(4-methylbenzenesulfonyl) (4-methylphenoxy) imidoyl] aziridine

Abstract: Aziridines are very important precursors to a wide range of biologically active molecules such as amino acids, antibiotics, alkaloids, and many others. 1 The two most important aspects of this class of compounds have been the stereo-regio-selectivity of their synthesis and energy barrier of nitrogen inversion. 1-3 Both aspects have very important effects on their physical and/or chemical behaviours. Lwowski and co-workers reported a highly stereoselective synthesis of aziridines via a reaction of imidoyl nitre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…NMR measurements, both in the gas phase and in solution, have shown that the rotational barrier in amides is strongly affected by the medium. ,, , Nevertheless, a different behavior was observed for tertiary carbamates if studied by dynamic NMR spectroscopy in solution: Actually, it has been found that the rotational barrier proved to be apparently insensitive to the solvent polarity. Recently, we reported dynamic 1 H NMR spectroscopy studies of various carbamates and other nitrogen-containing organic compounds. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NMR measurements, both in the gas phase and in solution, have shown that the rotational barrier in amides is strongly affected by the medium. ,, , Nevertheless, a different behavior was observed for tertiary carbamates if studied by dynamic NMR spectroscopy in solution: Actually, it has been found that the rotational barrier proved to be apparently insensitive to the solvent polarity. Recently, we reported dynamic 1 H NMR spectroscopy studies of various carbamates and other nitrogen-containing organic compounds. , …”
mentioning
confidence: 99%
“…The rate constants, k , for the present dynamic process in the carbamates 1a − d were calculated at the coalescence temperature ( T c ) employing the Gutowsky−Holm equation ( k c = πΔν/2 -1/2 ). ,,,,, Assuming the transmission coefficient, κ, to be unity, the free energies of activation (Δ G ⧧ ) were calculated according to the Eyring equation (Δ G ⧧ = RT c [ln T c − ln k c + 23.76]). ,,,,, …”
mentioning
confidence: 99%